JMHSB 2020
DOI: 10.33790/jmhsb1100121
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, Physical and Cardiovascular Components Associated with Immune Profile in Hispanic-Latino People Living with HIV

Abstract: HIV is associated with poor quality of life and high mortality rates on the people suffering from this illness. Presently, Cd4 levels are the main factor established to identify the distinct trauma on the host's body and systems. The consequence and severity of HIV complications vary among individuals; however, many factors come into play when assessing and developing treatment plans for this population.Purpose: The current investigation endeavors to respond to the following, are there any indicators of a weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…While the specificity of these modification patterns were not observed in our subjects, their apparent absence may be attributed to the cognitive symptomatology for depression being strikingly similar to the MCNAs that are inevitably present in those with HIV; among these found in PLHIV are the alterations to verbal skills, working memory, attention to information, speed of information processing, information retrieval, learning, personality and behavioral changes, executive functioning, and motor skills, as reported by Mitra and Sharman [21]. Recent findings have also underscored the role of depression as a principal cause of MCNAs in PLHIV [57]. As such, associations made between cognitive functioning disruptions from depression in HIV-infected individuals have been ineffectual thus far [58], as the identical signs and symptoms make it difficult to distinguish whether the alterations are depression-induced or stem from the virus, itself.…”
Section: Discussionmentioning
confidence: 63%
“…While the specificity of these modification patterns were not observed in our subjects, their apparent absence may be attributed to the cognitive symptomatology for depression being strikingly similar to the MCNAs that are inevitably present in those with HIV; among these found in PLHIV are the alterations to verbal skills, working memory, attention to information, speed of information processing, information retrieval, learning, personality and behavioral changes, executive functioning, and motor skills, as reported by Mitra and Sharman [21]. Recent findings have also underscored the role of depression as a principal cause of MCNAs in PLHIV [57]. As such, associations made between cognitive functioning disruptions from depression in HIV-infected individuals have been ineffectual thus far [58], as the identical signs and symptoms make it difficult to distinguish whether the alterations are depression-induced or stem from the virus, itself.…”
Section: Discussionmentioning
confidence: 63%
“…Records of participants who met the following criteria were included in the current study: 1) between the ages of 18-65, 2) had a CD4 count greater than 200 cells per cubic millimeter, 3) were a community ambulators, and 4) actively participating in an antiretroviral therapy protocol. A cut-off age of 65 was used in this study because previous studies have found that age is inversely related to cardiorespiratory fitness [17,22]. Participants were excluded from the study for the following reasons: if the participant 1) was pregnant, 2) reported a history of hospitalization within the last six months, 3) reported a history of musculoskeletal injury or surgery in the past six months, and 4) had an HIV dementia diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Low levels of cardiorespiratory fitness are associated with increased risk for mortality and CVD [21]. In addition, previous studies have found that cardiorespiratory fitness is lower in PLHIV and inversely related to age, exposing PLHIV to greater health complications [14][15][16][17]22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study follows the Ross protocol used in previous studies by Rosario et al [15] and Rosario et al [16], which also recruited PLWH. Data retrieved from participants' records for this study included heart rate and blood pressure for the cardiovascular components and gait velocity and inclination for the motor components.…”
Section: Motor and Cardiovascular Componentsmentioning
confidence: 99%